2002
DOI: 10.1097/00005110-200211000-00006
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Empowerment and Selected Personality Characteristics to Nursing Job Satisfaction

Abstract: Through careful manipulation of the hospital environment, both structural and psychological empowerment can be increased, resulting in greater job and patient satisfaction and, ultimately, improved patient outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
164
2
8

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 157 publications
(188 citation statements)
references
References 22 publications
9
164
2
8
Order By: Relevance
“…In a recent study, 43 researchers found that nurses' perceptions of a positive organizational climate were associated with higher odds of BSI, another unexpected relationship. Although previous research has shown the importance of empowerment to nurses' outcomes, 44 our study is the first to try to link workplace empowerment to actual patients' outcomes. VAP may not be a nursing-sensitive outcome, as discussed earlier, and other variables to which VAP may be more sensitive were not included in the study.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, 43 researchers found that nurses' perceptions of a positive organizational climate were associated with higher odds of BSI, another unexpected relationship. Although previous research has shown the importance of empowerment to nurses' outcomes, 44 our study is the first to try to link workplace empowerment to actual patients' outcomes. VAP may not be a nursing-sensitive outcome, as discussed earlier, and other variables to which VAP may be more sensitive were not included in the study.…”
Section: Discussionmentioning
confidence: 99%
“…Employees should be strengthened with ample resources, leadership, encouraging workplace environment, which will in turn have a positive impact on job satisfaction and will results in adequate human force formation (Manojlovich & Laschinger, 2002). Empowerment and satisfaction with management are main predictors of worker's retention.…”
Section: Job Performancementioning
confidence: 99%
“…Management should understand the importance of job involvement because it is most important and essential component of work behavior among the workforce as prior research proved this phenomenon (Manojlovich, Laschinger, & Heather, 2002;Soong, 2000). It was highlighted that by giving employees power over their work content i.e.…”
Section: Job Involvementmentioning
confidence: 99%